The antioxidant activity of polysaccharides: A structure-function relationship overview - Fernandes, Pedro A.R.; Coimbra, Manuel A. (Carbohydrate polymers, 2023)
Over the last years, polysaccharides have been linked to antioxidant effects using both in vitro chemical and biological models. The reported structures, claimed to act as antioxidants, comprise chitosan, pectic polysaccharides, glucans, mannoproteins, alginates, fucoidans, and many others of all type of biological sources. The structural features linked to the antioxidant action include the polysaccharide charge, molecular weight, and the occurrence of non-carbohydrate substituents. The establishment of structure/function relationships can be, however, biased by secondary phenomena that tailor polysaccharides behavior in antioxidant systems. In this sense, this review confronts some basic concepts of polysaccharides chemistry with the current claim of carbohydrates as antioxidants. It critically discusses how the fine structure and properties of polysaccharides can define polysaccharides as antioxidants. Polysaccharides antioxidant action is highly dependent on their solubility, sugar ring structure, molecular weight, occurrence of positive or negatively charged groups, protein moieties and covalently linked phenolic compounds. However, the occurrence of phenolic compounds and protein as contaminants leads to misleading results in methodologies often used for screening and characterization purposes, as well as in vivo models. Despite falling in the concept of antioxidants, the role of polysaccharides must be well defined according with the matrices where they are involved. [Display omitted]